Microcontroller based car usage authentication and activity monitoring with the use of driver's license and finger print matching - Asio, Romnick P. (Animo Repository, 2008)
Innovations on cars never stop. Continuously, innovators are being more and more creative with their ideas in improving certain systems in automobiles. Monitoring a car's activities may seem not that important for most people but when it comes to the industry where a lot of cars are being used, monitoring them would prove quite a challenge these goes to car rental businesses, taxi companies and etc. The Philippine driver's license that people use today looks simple and most people do not know that their license may be scanned or read electronically. But in contrast to its appearance, it has advanced technology regarding data gathering through its innovative barcode symbology. These technology embedded in the Philippine driver's license have limitless potential. By just simply reading the barcode, valuable data can be gathered instantly from the card holder's name down to its expiry date. The data gathered can be used in many different ways. Together with the monitoring issue the group found a way to make these things helpful to people in such a way of unlocking further potentials for automobile add ons.